2020
DOI: 10.3390/jcm9113638
|View full text |Cite
|
Sign up to set email alerts
|

What Opinions Do Tumor Reconstructive Surgeons Have about Sports Activity after Megaprosthetic Replacement in Hip and Knee? Results of the MoReSports Expert Opinion Online Survey

Abstract: Sports activity has many benefits in cancer survivors. A key one is having sport activity contribute to the well-being of the individual. However, there are no guidelines about the intensity and kind of postoperative mobility workouts after hip or knee megaprosthetic treatment. Opinion research about sports after modular bone and joint replacement may provide an understanding of surgeons’ attitudes on sports activity after megaprostheses of the hip and knee joint. A web survey with members of three internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…As of 2006, silver-coated implants were available and used in all patients [15]. As of 2010, implants for reverse shoulder reconstruction were available and used in patients in whom the axillary nerve and a sufficient portion of the deltoid could be preserved [11][12][13].…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…As of 2006, silver-coated implants were available and used in all patients [15]. As of 2010, implants for reverse shoulder reconstruction were available and used in patients in whom the axillary nerve and a sufficient portion of the deltoid could be preserved [11][12][13].…”
Section: Surgical Techniquementioning
confidence: 99%
“…These achievements have subsequently led to an increased interest in patients' postoperative function and return to sports activities and the potential factors associated with a successful return to sports activities-especially considering that mostly young patients are affected by primary bone sarcomas [7][8][9][10]. However, while sports activities in sarcoma patients who have undergone megaprosthetic reconstruction have previously been studied for lower extremity tumours, there is a paucity of studies on upper extremity reconstructions, particularly studies applying homogeneous inclusion criteria and larger patient cohorts [11,12]. Furthermore, patient-and procedure-related factors associated with outcome are widely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sports activities that are practiced without prosthesis were skiing, sitting volleyball and swimming. In comparison, Hobusch et al reported that patients with EPR mostly returned to low impact sports activities only [24] because they try to protect their EPR from a revision operation or an activity associated injury [23]. Nevertheless, rotationplasty is currently performed rarely.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that onesided intensive exercise is a possible intervention to reduce the risk of hip fractures in healthy women. Hobusch et al [18] recommend four to seven sports after surgery, depending on the type of surgery on the thighs or knees. Timpka et al [19] studied injuries in football.…”
mentioning
confidence: 99%